Retention in care prior to antiretroviral treatment eligibility in sub-Saharan Africa: a systematic review of the literature. Issue 6 (24th June 2015) - Plazy, Mélanie; Orne-Gliemann, Joanna; Dabis, François; Dray-Spira, Rosemary
Abstract : Objective: We aimed at summarising rates and factors associated with retention in HIV care prior to antiretroviral treatment (ART) eligibility in sub-Saharan Africa. Design: We conducted a systematic literature review (2002–2014). We searched Medline/Pubmed, Scopus and Web of Science, as well as proceedings of conferences. We included all original research studies published in peer-reviewed journals, which used quantitative indicators of retention in care prior to ART eligibility. Participants: People not yet eligible for ART. Primary and secondary outcomes: Rate of retention in HIV care prior to ART eligibility and associated factors. Results: 10 papers and 2 abstracts were included. Most studies were conducted in Southern and Eastern Africa between 2004 and 2011 and reported retention rates in pre-ART care up to the second CD4 measurement. Definition of retention in HIV care prior to ART eligibility differed substantially across studies. Retention rates ranged between 23% and 88% based on series ranging from 112 to 10 314 individuals; retention was higher in women, individuals aged >25 years, those with low CD4 count, high body mass index or co-infected with tuberculosis, and in settings with free cotrimoxazole use. Conclusions: Retention in HIV care prior to ART eligibility in sub-Saharan Africa has been insufficiently described so far leaving major research gaps, especially regarding long-term retention rates and sociodemographic, economic, clinical and programmatic logistic determinants. The prospective follow-up of newly diagnosed individuals is required to better evaluate attrition prior to ART eligibility among HIV-infected people.